PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN EFIKASI DIRI TERHADAP MINAT WIRAUSAHA - Dede Kurnia; Kusnendi Kusnendi; Chairul Furqon (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The purpose of this study was to analyze the effect of entrepreneurial knowledge and self-efficacy on entrepreneurial intention in SMK Serba Bakti, Tasikmalaya. Technically, the method used in this study is a form of quantitative research with post facto research design. The study participants were students of class XI SMK Serba Bakti, Tasikmalaya. The data used in this study was collected through questionnaires. The data collected, then analyzed by using multiple regression analysis with a significance value of 5%. The findings of the study show that entrepreneurial knowledge and self-efficacy have a positive effect on the entrepreneurial intention in SMK Serba Bakti, TasikmalayaKeyword: Entrepreneurial Knowledge, Self-Efficacy, Entrepreneurial